The Consequences Of Social Comparison On Price-Quality Schema, Prestige Sensitivity, And Willingness To Purchase - Burhanudin Burhanudin; Shalva Sabrina Putri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Consumers interact with other consumers and often compare themselves with others. This consumer tendency shows social comparison. Masstige, which stands for prestige for the masses, may involve this case. However, it has received less attention in previous studies. This study examines the consequences of social comparison on price-quality schema, prestige sensitivity, and willingness to purchase a masstige brand. This study also examines the mediation of price-quality schema and prestige sensitivity on the effect of social comparison on willingness to purchase. A consumer survey was conducted to test these effects, and 240 respondents participated. The data in this study were analyzed using structural equation modeling. The analysis results show that social comparison affects price-quality schema and prestige sensitivity and subsequently affects willingness to purchase. This study also found mediation of price-quality schema and prestige sensitivity on the effect of social comparison on willingness to purchase. The above findings indicate that marketers of masstige brands can utilize social comparison to market their products.